LANGUAGE AND CONFLICT MANAGEMENT AMONG THE ANAANG PEOPLE - Silas, Peter. A.; Abru, John O. (EBSU Journal of Social Sciences and Humanities, 2024)
The study sets out to investigate how the contextual or the speaker-intended interpretations assigned to utterances used in conflict situations in the Anaang society impact on parties in a conflict situation to resolve the conflict. Decoding the locally situated meanings and cultural relevance of utterances in conflict situation has been a problem because mediators often use words figuratively with contextual relevance. The data were collected through participant observations, unstructured interviews and secondary sources. The work employed ethnopragmatics and speech act theory. The study explicates the efficacy of Anaang proverbs in conflict management and enhances a better understanding of the Anaang pragmatic use of language with the intrinsic nature of the imbued cultural values. The study revealed that language for conflict management in Anaang expresses principles that govern life, ethical values and beliefs. It further illustrates the ability of the people to make statements of wisdom using locally sourced contents imbued with concepts and interpretations which convey social values to enhance social control and harmony. The study recommends incorporating teaching of proverbs into school curriculum at different levels of our educational system.